A Topic Dermatitis and Gastrointestinal Diseases (Texas Journal of Medical Science, 2022)
One of the peculiarities of chronic diseases of the gastrointestinal tract (GIT) in children is their comorbid course. The link between allergic diseases and the digestive system is of particular interest. It is assumed that direct allergic injury to the mucous membranes of the esophagus, stomach and intestines by various allergens, damage to other organs and simultaneous development of local inflammation may occur with increased permeability of the epithelial barrier of the gastrointestinal tract to allergens. Because the gastric mucosa is in contact with allergens that enter before other digestive organs, the combination of these allergic diseases and AID pathology is attracting the attention of researchers today.